2016
DOI: 10.1002/ptr.5731
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic and Pharmacodynamic Interaction of Andrographolide and Standardized Extract of Andrographis paniculata (Nees) with Nabumetone in Wistar Rats

Abstract: The aim of the study was to investigate the herb-drug interaction of Andrographis paniculata Nees (Acanthaceae) and Andrographolide (AN) with nabumetone (NAB) in wistar rats. Pharmacokinetic and pharmacodynamic interactions were studied after co-administration of APE and AN with NAB in Wistar rats. In pharmacokinetic studies, significant decrease in Cmax, AUC and AUC of 6-MNA after co-administration with pure AN and APE has been observed. T of 6-MNA has been increased to 2 h from 1.5 h in AN + NAB treated grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…By contrast, another study on HDIs with nabumetone via a pharmacodynamics assay showed that the antiarthritic activity significantly decreased; similarly, several pharmacokinetic profiles (C max , AUC, and T½) decreased (30). The reduction in some of these pharmacokinetic parameters was not supported by a statistically significant increase in volume distribution.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…By contrast, another study on HDIs with nabumetone via a pharmacodynamics assay showed that the antiarthritic activity significantly decreased; similarly, several pharmacokinetic profiles (C max , AUC, and T½) decreased (30). The reduction in some of these pharmacokinetic parameters was not supported by a statistically significant increase in volume distribution.…”
Section: Resultsmentioning
confidence: 85%
“…The pharmacokinetic interaction mechanism involving the CYP1A2 enzyme from APE and AND has also been proven in several anti-inflammatory drugs, such as etoricoxib, nabumetone, and naproxen (28)(29)(30). These drugs are metabolized primarily through the CYP1A2 enzyme activity pathway in mice and other enzymes, such as CYP2A6, CYP2C9, CYPC19, CYP2D6, and CYP3A4, expressed in humans (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, antiarthritic activity of andrographolide is observed in Wistar rats F I G U R E 5 Schematic diagram of antioxidant activity of andrographolide. AG, andrographolide; MAPK, mitogenactivated protein kinase; AKT, isoform of protein kinase B; mTOR, mechanistic target of rapamycin; EGFR, epidermal growth factor receptor; FasL, Fas ligand; PI3K, phosphoinositide 3-kinases; PDK1, pyruvate dehydrogenase kinase 1; JAK, Janus kinases; STAT3, signal transducer and activator of transcription proteins 3; BCL2, B-cell lymphoma 2 when administered orally in combination with Nabumetone [61]. The anti-inflammatory effect of andrographolide was investigated in hyperglycemia (HG)-induced HUVEC 12 cell lines.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…In an in vitro experiment, andrographolide (50 mg/kg) accelerated apoptosis and autophagy of neutrophil extracellular traps formed during rheumatoid arthritis [60]. Similarly, antiarthritic activity of andrographolide is observed in Wistar rats when administered orally in combination with Nabumetone [61]. The anti‐inflammatory effect of andrographolide was investigated in hyperglycemia (HG)‐induced HUVEC 12 cell lines.…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…Radiotracer and auto-radiographic methods were also used to study the bio-distribution pattern of 6-MNA and its pharmacokinetic profile (Haddock et al, 1984(Haddock et al, , 1983. Simultaneous determination of 6-MNA and herbal components were also reported using modified HPLC method (Balap et al, 2016). Binary and ternary solid dispersions of NBT prepared by melt-method that exhibited better product characteristics upon evaluation were chosen for in-vivo studies to find out the bioavailability.…”
mentioning
confidence: 99%